Mathematical model for predicting fungal growth and decomposition rates based on improved Logistic equations - Pan, Jiayong; Le, Wenxin; Wang, Zi'ao; Chen, Jian (International Journal of Agricultural and Biological Engineering, 2023)
As the function of the decomposition of fungi has been clearly researched in the global carbon cycle, it is obviously of value to explore the decomposition rate of fungal populations. This study analyzed the relationship between environmental factors and biodiversity step by step. In order to explore the interaction between the fungi and the relationship between the decomposition rate of fungi with time, the model based on the Logistic model was built and the Lotka-Volterra model was employed in the condition of two kinds of fungi existing in an environment with limited resources. The changing trend of population number and decomposition rate of several fungi under different environmental conditions can be predicted through the model. To illustrate the applicability of the model, Laetiporus conifericola and Hyphoderma setigerum were applied as examples. The results showed that the higher the degree of population diversity, the greater the decomposition rate, and the higher the decomposition efficiency of the ecosystem. Its rich species diversity is conducive to accelerating the decomposition of litter, lignocellulose, and the circulation of the entire ecosystem. Based on the above model and using the data from measuring the mycelial elongation rate of each isolate at 10°C, 16°C, and 22°C under standardized laboratory conditions, the growth patterns of the five fungi combinations were simulated. The results revealed a general increase in growth rate with increasing temperature, which verifies the accuracy of the model. Moreover, it also revealed that the total decomposition rate after fungal incorporation was negatively correlated with the decomposition rate of a fungal single action. Based on the above model, predictions can be made for fungal growth in different environments, and suitable environments for fungal growth can be determined. In the future, the model can be further optimized, and lignin and cellulose decomposition factors can be added to fit the decomposition of logs. The application scenarios of the model can be further broadened, which can contribute to the restoration and management of the ecological environment, as well as produce good effects in the fields of fungi assisting the global carbon cycle and soil problem restoration.Keywords: Logistic equations, fungal decomposition, fungal growth, mathematical modelDOI: 10.25165/j.ijabe.20231601.7405Citation: Pan J Y, Le W X, Wang Z A, Chen J. Mathematical model for predicting fungal growth and decomposition rates based on improved Logistic equations. Int J Agric & Biol Eng, 2023; 16(1): 60–65.